Proceso de atención de enfermería en paciente de 34 años de edad con tuberculosis extrapulmonar. - Dávila Hidalgo, Sara Michelez (2020)
Through this clinical case analysis, he describes extra pulmonary tuberculosis as it continues to be a public health problem. This work presents detailed information of my 34-year-old patient diagnosed with Extrapulmonary tuberculosis, the nursing care process is applied and a plan of care and nursing interventions are carried out to have optimal care of the pathology which focuses. In this way, individualized comprehensive care, emotional support, monitoring and periodic follow-ups are contributed to evaluate the evolution of health actions, and thus to promote the self-care of therapeutic management for my patient.